PERAN PENGAJARAN PENDIDIKAN ISLAM DI LINGKUNGAN MAJLIS TALIM NURUL JANNAH KOMPLEK PERUMAHAN KELAPA DUA TANGERANG - Siti Maryam; Neneng Aida Rosyidah; Hasanudin Hasanudin (Ta'dibiya, 2023)
Majlis Ta'lim is very closely related to society where in a Majlis Ta'lim there will be social interaction between the speaker and the congregation, as well as between congregations. In the local community, the recitation is only attended by a group of women or mothers whose reception, especially enlightenment, is less than optimal and optimal. However, this did not happen at the Nurul Jannah ta'lim majlis in the Kelapa Dua Tangerang housing complex, which in fact is the biggest advantage of the presence of recitations with the teaching of Islamic education which is able to reflect the norms of good religious life in social life. This research method uses qualitative methods, including observation, interviews and documentation. Based on the results of this research, it is clear that the recitation of Islamic education has an impact on the community environment, the complex environment especially has an impact on the behavior of the women of the Majlis Ta'lim as parents, they must pay attention to their children's behavior and care about their children's education. Furthermore, the Majlis Ta'lim has provided humanist services through teachers or material providers so that the learning process will run conducively and the quality will increase. Not only is the role of the Majlis Ta'lim but also the Islamic education delivered helps improve discipline and understanding of Islam.